CT Angiography-Based Radiomics for Classification of Intracranial Aneurysm Rupture - Alwalid, Osamah; Long, Xi; Xie, Mingfei; Yang, Jiehua; Cen, Chunyuan; Liu, Huan; Han, Ping (Frontiers in Neurology, 2021)
Background: Intracranial aneurysm rupture is a devastating medical event with a high morbidity and mortality rate. Thus, timely detection and management are critical. The present study aimed to identify the aneurysm radiomics features associated with rupture and to build and evaluate a radiomics classification model of aneurysm rupture. Methods: Radiomics analysis was applied to CT angiography (CTA) images of 393 patients (152 [38.7%] with ruptured aneurysms). Patients were divided at a ratio of 7:3 into retrospective training (n=274) and prospective test (n=119) cohorts. A total of 1229 radiomics features were automatically calculated from each aneurysm. The features number was systematically reduced and the most important classifying features were selected. A logistic regression model was constructed using the selected features and evaluated on training and test cohorts. Radiomics score (Rad-score) was calculated for each patient and compared between ruptured and unruptured aneurysms. Results: Nine radiomics features were selected from the CTA images and used to build the logistic regression model. The radiomics model has shown good performance in the classification of the aneurysm rupture on training and test cohorts (area under the receiver operating characteristic curve: 0.92 [95% confidence interval CI: 0.89-0.95] and 0.86 [95% CI: 0.80-0.93], respectively, p < 0.001). Rad-score showed statistically significant differences between ruptured and unruptured aneurysms (median, 2.50 vs. -1.60 and 2.35 vs. -1.01 on training and test cohorts, respectively, p < 0.001). Conclusion: The results indicated the potential of aneurysm radiomics features for automatic classification of aneurysm rupture on CTA images.